Synthesis and Evaluation of TiO2/Chitosan Based Hydrogel for the Adsorptional Photocatalytic Degradation of Azo and Anthraquinone Dye under UV Light Irradiation. (2016) - Dhanya, A.; Aparna, K.
Abstract: The high rate of electron/hole pair recombination while using TiO2 as a photocatalyst reduces the quantum yield of the process. Adding a co-adsorbent can increase the photocatalytic efficiency of TiO2 . In this study, a composite of TiO2 /Chitosan were synthesised in which chitosan also acts as an immobilization agent. The characterization of TiO2 nanoparticles is done using Scanning Electron Micrograph and energy dispersive x-ray spectroscopy measurements. The experimental results show that TiO2 nanoparticles encapsulated in Chitosan can remove the dyes from wastewater almost entirely. The parameters that affect the degradation process are initial concentration of the dye solution, contact time, catalyst concentration, effect of ions and pH. While using TiO2 in slurry form requires separation of the photocatalyst from the treated solution, while in the immobilization technique, the requirement of separation can be avoided.